« Humane nature condicio sic miserabilis » - Mathilde Baron (Mélanges de la Casa de Velázquez, 2013)
This article uses an archive document to look at the networks of influence woven around the Aragonese monarchs at the turn of the 15th-16th centuries. It highlights the mechanisms and the motivations behind a particular kind of judicial decision—the royal pardon. Adopting a micro-historical approach, it describes the relationships forged between the monarchs of Aragon and a converso family of Zaragoza: from father to son, from moneylender to chronicler, the García de Santa Marías demonstrated their loyalty to the Crown by placing first their money and then their pens at their sovereign’s service; the mutual dependence of the monarch and his moneylenders was born of the former’s pressing need for liquid funds and on the latter’s need for protection. From a standpoint of literary history, this article fills out the scanty biographical information available on the Aragonese Gonzalo García de Santa María and helps place some of his historiographic work in context.